On Front Mutation in the System of Old English Diphthongs - Забулене, Лайма (Kalbotyra, 1981)
Front mutation affected OE diphthongs originating from the West Germanic diphthongs au, eu, iu, and short and long diphthongs arising from breaking and front diphthongization. It might be assumed that the initial results of front mutation were identical in all OE dialects, and that dialectal differences appeared only in the course of later development. Our assumption rests on the fact that West Saxon preserves the original positional variation of phonemes to a greater extent than the other OE dialects. We may conclude that front mutation enriched the morphological structure of OE with new grammatical models which, however, remained exclusively characteristic of the West Saxon dialect.